(untitled) (Fiep Bulletin - online, 2024)
Through the body’s natural development, the aging process reaches all individuals, whether they are physically active or not, and the sarcopenic process comes with it, in an inherent way to aging. Aiming to understand and foster the debate about the impact of physical activity, more precisely of strength training, in containing the advances of sarcopenia for the elderly, this research was carried out. That said, the study focused on literary and comparative analysis between selected articles that contemplated descriptors related to aging, sarcopenia and strength training and that exclusively considered this physical practice in the responsive analysis of elderly people against sarcopenic advancement. Through the comparison between articles and the analyzes made, it became possible to affirm that the practice of strength training for the elderly has numerous benefits, among them, the improvement in musculature, bone density, motor coordination, as well as quality of life. However, it is worth reiterating that, in order to make it possible to implement this practice for the elderly population, specific knowledge that physical education professionals have is needed. Keywords: Aging. Strength training. Sarcopenia. Physical education professional.